Soil Science Treatise - Sathyanarayana,Eetela [et al.] (New Delhi; Jaya Publishing House, 2021)
1. PEDOLOGY 2. SOIL PHYSICS 3. SOIL CHEMISTRY 4. SOIL FERTILITY 5. SOIL MICROBIOLOGY 6. ANALYTICAL CHEMISTRY 9. APPENDIX 8. IMPORTANT POINTS 9. MEMORY BASED QUESTIONS [ASRB MAINS - 1999] 10. MEMORY BASED QUESTIONS [ASRB MAINS - 2001] 11. MEMORY BASED QUESTIONS [ASRB MAINS - 2003] 12. MEMORY BASED QUESTIONS [ASRB MAINS - 2005] 13. MEMORY BASED QUESTIONS [ASRB MAINS - 2006] 14. MEMORY BASED QUESTIONS [ASRB MAINS - 2007] 15. MEMORY BASED QUESTIONS [ASRB MAINS - 2009] .16. MEMORY BASED QUESTIONS [ASRB MAINS - 2010] 17. MEMORY BASED QUESTIONS [ASRB MAINS - 2011] 18. SOIL FACTS